2009
DOI: 10.1007/s11104-009-0200-1
|View full text |Cite
|
Sign up to set email alerts
|

Testing the ecological stability of ectomycorrhizal symbiosis: effects of heat, ash and mycorrhizal colonization on Pinus muricata seedling performance

Abstract: Understanding how abiotic conditions mediate the outcome of biotic interactions is a key question in community ecology. This is particularly interesting in the case of mutualisms because changing environmental conditions may be a source of evolutionary or ecological instability in the relationship between symbiotic partners. For the mycorrhizal symbiosis, elevated nutrient levels may make the carbon cost to plants of supporting mycorrhizal fungi outweigh the benefits of mycorrhizal nutrient acquisition. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…Although Kipfer et al ( 2012 ) found that the most enzymatically active fungus in their study, Suillus granulatus , had a positive effect on seedling growth, we did not observe statistically significant differences in growth by treatment in our study. In part, this was likely due to the homogeneous, high-quality soil environment created by autoclaving the experimental soils, which can release substantial amounts of nutrients into plant-accessible pools, reducing the impact of EMF on seedling growth ( Peay, Bruns & Garbelotto , 2010 ) and plant carbon allocation to EMF ( Hobbie , 2006 ). Other studies have found no relationship between EMF competitiveness and seedling growth ( Kennedy, Peay & Bruns , 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although Kipfer et al ( 2012 ) found that the most enzymatically active fungus in their study, Suillus granulatus , had a positive effect on seedling growth, we did not observe statistically significant differences in growth by treatment in our study. In part, this was likely due to the homogeneous, high-quality soil environment created by autoclaving the experimental soils, which can release substantial amounts of nutrients into plant-accessible pools, reducing the impact of EMF on seedling growth ( Peay, Bruns & Garbelotto , 2010 ) and plant carbon allocation to EMF ( Hobbie , 2006 ). Other studies have found no relationship between EMF competitiveness and seedling growth ( Kennedy, Peay & Bruns , 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…The cost to benefit ratio of the ectomycorrhizal symbiosis has been shown to change under different environmental conditions ( Kennedy and Peay, 2007 ), and host plants have been shown to regulate their EMF partners under changing environmental conditions. For example, Peay et al (2010) found that seedlings were able to maintain high growth rates under experimental nutrient enrichment by reducing colonization by EMF of the genus Rhizopogon . Across a natural environmental gradient, Moeller et al (2013) found that the traits of EMF reflected the nutritional needs of their host plants, with communities composed of efficient foragers with high carbon requirements dominating in nutrient deficient soils.…”
Section: Discussionmentioning
confidence: 99%
“…Across a natural environmental gradient, Moeller et al (2013) found that the traits of EMF reflected the nutritional needs of their host plants, with communities composed of efficient foragers with high carbon requirements dominating in nutrient deficient soils. Because Geopora is a common member of the EMF communities found on pinyons, trees on which less efficient mutualists were eliminated were able to maintain higher growth rates as in Peay et al (2010) . The strong positive relationship observed between dominance by Geopora and pinyon growth suggests that although community disassembly was often considered detrimental ( Zavaleta et al, 2009 ), negative effects may not always be observed, at least in the short term.…”
Section: Discussionmentioning
confidence: 99%
“…Although Kipfer et al (2012) found that the most enzymatically active fungus in their study, Suillus granulatus, had a positive effect on seedling growth, we did not observe statistically significant differences in growth by treatment in our study. In part, this was likely due to the homogeneous, high-quality soil environment created by autoclaving the experimental soils, which can release substantial amounts of nutrients into plant-accessible pools, reducing the impact of EMF on seedling growth (Peay, Bruns & Garbelotto, 2010) and plant carbon allocation to EMF (Hobbie, 2006). Other studies have found no relationship between EMF competitiveness and seedling growth (Kennedy, Peay & Bruns, 2009).…”
Section: Discussionmentioning
confidence: 97%